The Effect of Corruption Prevention Efforts with Regional Corruption Cases and Complaints - Astuti, Dwi Aprillia Linda; Winoto, Joyo; Suprehatin, Suprehatin (International Journal Labs, 2023)
One of the obstacles in the business sector in Indonesia is corruption. Efforts to eradicate corruption are carried out through education, prevention and prosecution strategies or known as the TRISULA strategy. One of the corruption prevention efforts carried out by the KPK is through the Monitoring Center for Prevention (MCP) with eight areas. This study aims to analyze the relationship between prevention and complaints and regional corruption cases. This study uses secondary data. Secondary data consists of the Regional Corruption Prevention Index, complaints, and regional corruption cases handled by the KPK in 34 provinces in Indonesia, 2018 – 2022. Primary data was obtained through a survey with purposive sampling in 22 local governments. Data were analyzed using regression analysis with e-VIEWS software. The results of the study show that the areas of prevention that have an influence on corruption complaints are planning and budgeting, procurement of goods and services, supervision of the Government Internal Supervisory Apparatus (APIP), and management of regional property. The prevention area that has an influence on corruption cases is the procurement of goods and services.